The involvement of CgCaspase-3 in regulating the expressions of proinflammatory cytokines through NF-κB/Rel signaling pathway in oysters - Zihan Wang; Xiaopeng Li; Jiejie Sun; Shuyi Mu; Wei Wu; Renle Chang; Lingling Wang; Linsheng Song (Comparative Immunology Reports)
Cysteinyl aspartate specific proteinase-3 (Caspase-3) is a prominent mediator of apoptosis and participates in the cell death signaling cascade. In our previous study, CgCaspase-3 identified from Crassostrea gigas was involved in CgGSDME-dependent pyroptosis. In the present study, CgCaspase-3 was demonstrated to regulate the expressions of proinflammatory cytokines through nuclear factor kappa B (NF-κB) signaling pathway. In haemocytes of Ac-DEVD-CHO-treated and CgCaspase-3-RNAi oysters, the nuclear translocation of NF-κB/Rel was inhibited at 24 h after Vibrio splendidus stimulation. The mRNA expressions of interleukins 17s (CgIL17–2, CgIL17–3, and CgIL17–6), tumor necrosis factor-1 (CgTNF-1), high mobility group box-1 protein (CgHMGB1) and interferon-like protein (CgIFNLP) were significantly decreased in haemocytes of CgCaspase-3-RNAi or CgRel-RNAi oysters, respectively. In addition, the phenomenon of gill swelling and cilia shedding was reduced in CgCaspase-3-RNAi oysters after V. splendidus stimulation. These results indicated that CgCaspase-3 was involved in regulating bacteria-induced inflammation through NF-κB/Rel signaling pathway.